2015
DOI: 10.1038/nature16165
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphorylation and linear ubiquitin direct A20 inhibition of inflammation

Abstract: Inactivation of the TNFAIP3 gene, encoding the A20 protein, is associated with critical inflammatory diseases including multiple sclerosis, rheumatoid arthritis and Crohn's disease. However, the role of A20 in attenuating inflammatory signalling is unclear owing to paradoxical in vitro and in vivo findings. Here we utilize genetically engineered mice bearing mutations in the A20 ovarian tumour (OTU)-type deubiquitinase domain or in the zinc finger-4 (ZnF4) ubiquitin-binding motif to investigate these discrepan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
243
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(255 citation statements)
references
References 50 publications
11
243
1
Order By: Relevance
“…S5C). RIPK1 and TNFR1 require the assembly of K63 and linear polyubiquitin chains for proper signaling activity, and they are subject to deubiquitination by A20 and OTULIN (14). The K63 ubiquitination of RIPK1 was not affected by the presence of mutant OTULIN proteins (Fig.…”
Section: Significancementioning
confidence: 91%
See 1 more Smart Citation
“…S5C). RIPK1 and TNFR1 require the assembly of K63 and linear polyubiquitin chains for proper signaling activity, and they are subject to deubiquitination by A20 and OTULIN (14). The K63 ubiquitination of RIPK1 was not affected by the presence of mutant OTULIN proteins (Fig.…”
Section: Significancementioning
confidence: 91%
“…S4 B and C). OTULIN cleaves Met1-linked linear polyubiquitin chains from target substrates, such as NEMO (IKKγ), RIPK1, ASC, and TNFR1 to restrict signaling activation and propagation (7,14,15). To investigate the effect of OTULIN mutations on its deubiquitinase function, we cotransfected WT and mutant OTULIN plasmids into HEK293 cells along with plasmids encoding the LUBAC subunits, mono specific-ubiquitin plasmid, and each of the OTULIN substrates NEMO (Fig.…”
Section: Significancementioning
confidence: 99%
“…TNFAIP3, an immediate early response gene, serves a critical role in the negative regulation of the NF-κB signaling pathway, as well as in β cell protection, through its actions as a dual ubiquitin-editing protein (49,57). The mechanism through which TNFAIP3 turns off inflammation signaling has previously been described as the disruption of ubiquitin enzyme complexes (58); in cells expressing deficient or mutant TNFAIP3 protein, there is defective removal of Lys63-linked ubiquitin from ubiquitin enzyme complexes following stimulation with TNF (59). Our previous study found that the plasma levels of TNF-α and IL-1β were significantly increased, and TNFAIP3 mRNA and protein expression levels were significant decreased in the peripheral blood mononuclear cells of diabetes patients (60).…”
Section: A B Cmentioning
confidence: 99%
“…2 and 3 Fig. 3; Wertz et al, 2015). However, four cysteines (i.e., C X4 C X11 C X2 C and C X2 C X11 C X2 C) in seven regions similar to the human Zf domains were well-conserved in fish.…”
Section: Structural Analysis Of Fugu A20 Genementioning
confidence: 98%